The relationship of germanium concentrations and the thickness of the c8h coal seam of the Dniprovska coal mine - Ishkov, V. V.; Kozii, Ye. S.; Chernobuk, O. I.; Pashchenko, P. S. (Інтеграл, 2022)
The research devoted to the study and analysis of the influence of the thickness for the с8н coal seam the Dniprovska coal mine on the content of germanium and elaboration of an objective (natural) typifying of the coal seam areas of different thickness according to the element’s concentration. The study is based on the data set of 370 samples of germanium and other impurity elements (so called "small elements") as well as measurements of seam thickness, ash content and sulfur content of coal performed in the central certified laboratories of geological production and exploration enterprises of Ukraine derived from the matter of formation samples obtained by production and research enterprises and companies. In order to bring the samples to the same scale, the raw data were normalized. In order to achieve the purpose of the study laboratory and statistical methods of research were applied, taking into account and interpreting the obtained results in terms of geological concept. During the research, the clustering of seam sections of different thickness according to germanium content was carried out using the weighted centroid median method, which was implemented in the statistical software platforms that provided the analysis of the clustering results.
Keywords: germanium; coal seam; regression analysis; cluster analysis; distribution histogram; normalized content